2010
DOI: 10.1007/s11095-010-0096-8
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2-Keap1 Signaling as a Potential Target for Chemoprevention of Inflammation-Associated Carcinogenesis

Abstract: Persistent inflammatory tissue damage is causally associated with each stage of carcinogenesis. Inflammation-induced generation of reactive oxygen species, reactive nitrogen species, and other reactive species not only cause DNA damage and subsequently mutations, but also stimulate proliferation of initiated cells and even metastasis and angiogenesis. Induction of cellular cytoprotective enzymes (e.g., heme oxygenase-1, NAD(P)H:quinone oxidoreductase, superoxide dismutase, glutathione-S-transferase, etc.) has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(104 citation statements)
references
References 123 publications
(139 reference statements)
1
103
0
Order By: Relevance
“…Furthermore, the expression of SOD1 in the lung, which is regulated by Nrf2 (ref. 26), was decreased by the PPE treatment, and subsequently restored by the concomitant treatment of animals with mepenzolate. This action of mepenzolate may also be involved in the observed decreased oxidative stress in vivo.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the expression of SOD1 in the lung, which is regulated by Nrf2 (ref. 26), was decreased by the PPE treatment, and subsequently restored by the concomitant treatment of animals with mepenzolate. This action of mepenzolate may also be involved in the observed decreased oxidative stress in vivo.…”
Section: Discussionmentioning
confidence: 91%
“…7c). It was reported that GST and its regulatory transcription factor, NF-E2-related factor 2 (Nrf2), in macrophages have an important role in the pathogenesis of COPD 25,26 . Therefore, we performed the Gene Set Enrichment Analysis using the custom gene set and confirmed that the downstream genes of Nrf2 (NFE2L2 target genes) were upregulated by the mepenzolate administration ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Constitutive CNC activity can be detrimental to reproduction and development (2,3), and tight regulation is thought to be achieved by controlling nuclear abundance, stability, posttranslational modification, and negative feedback (1,(3)(4)(5)(6)(7)(8). Mammalian Nrf2 is the best studied inducible CNC and is a popular therapeutic target for multiple age-and stress-related diseases (9)(10)(11). Nrf2 is regulated by a redox-sensitive ubiquitin ligase adaptor named Keap1 (5).…”
mentioning
confidence: 99%
“…The transcription of many detoxifying enzymes is regulated through the antioxidant response element (ARE), whose transcription factor, Nrf2, is repressed under basal conditions by Keap1 (24,74,75). Dietz et al, 2008, described how extracts from the roots of Angelica sinensis, induced the detoxiˆcation enzyme NAD(P)H: quinone oxidoreductase 1 (NQO1) by alkylating Keap1.…”
Section: Examples Of Mechanisms Of Anti-mutagen Protection Against DImentioning
confidence: 99%